2015
DOI: 10.1530/eje-15-0341
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate by serum cystatin C correlates with cardiometabolic parameters in patients with primary hyperparathyroidism

Abstract: Objective: Patients with primary hyperparathyroidism (PHPT) are at risk of chronic kidney disease (CKD). Cystatin C (Cys-C) is considered a more reliable tool to assess glomerular filtration rate (GFR) than creatinine. The study aimed to assess circulating Cys-C and its relationships with biochemical PHPT and cardiometabolic parameters. Design and methods: The present cross-sectional study was performed in academic endocrine units on PHPT patients (nZ190) and non-hypertensive, non-diabetic, age-and sex-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…This results indicate the higher sensitivity of cystatin C compared to creatinine in detecting renal function in patients with pHPT. Similar results were also shown by Ermetici et al ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…This results indicate the higher sensitivity of cystatin C compared to creatinine in detecting renal function in patients with pHPT. Similar results were also shown by Ermetici et al ( 31 ).…”
Section: Discussionsupporting
confidence: 92%
“…Nephrolithiasis, which is more common in males [ 127 ], is an indication for PTX [ 106 , 128 , 129 ]. Chronic kidney disease (CKD), a long-term complication of PHPT with a prevalence of 16–17% [ 130 ], is the expression of a severe phenotype and carries an increased risk of morbidity and mortality [ 102 ] due to its association with hypertension, decreased BMD, and worse diabetic status [ 131 ]. PTH levels are associated with the degree of renal impairment in PHPT [ 132 ], and PTX prevents further kidney impairment [ 133 ].…”
Section: Evidence For a Role Of Pth In Conditions Of Abnormal Pth mentioning
confidence: 99%
“…Prolonged hypercalcaemia was considered to impair kidney function, and a reduced glomerular filtration rate was common in advanced severe PHPT (27,28). Supporting the connection between PHPT and renal impairment, in the PEARS cohort of 1424 asymptomatic PHPT patients and 7120 controls, serum creatinine at diagnosis is predictive of mortality at a 3-year term, the (42,43). Evaluation of kidney function in PHPT patients by measurement of cystatin C, a low-molecularweight protein secreted by nearly all cells, freely filtered at renal glomerular level and then metabolized by the proximal tubule, which is considered a more reliable tool to assess GFR than serum creatinine, showed that the most evident determinant of circulating cystatin C …”
Section: Kidney Function In Phpt Patientsmentioning
confidence: 99%